The Xanthine Oxidase Inhibitory Activities of Natural-Based Compounds Targeting Gout - Dedeoğlu, Nurcan (Current Research in Pharmacy and Pharmaceutical Sciences II-2024, 2024)
This chapter starts with an overview of the chapter and then delves into the causes of gout and its treatment. The main treatment for gout is to inhibit xanthine oxidase activity by allopurinole. Given the risk factors associated with using allopathic medications to treat this illness, the discussion has evolved into a unique problem. In this context, the focus of this chapter is to introduce advances in research on natural products for anti-gout treatment. This chapter will assist in the analysis of active anti-gout ingredients while also providing guidance for further development and research of anti-gout drugs. Worldwide, the prevalence of hyperuricemia is increasing as a result of rising living standards and altered dietary habits. Elevated levels of uric acid can lead to conditions like gout and kidney stones, which call for prompt medical attention. Research on active ingredients (extracts) or monomer compounds derived from natural products has grown significantly in importance. Natural products are favored in scientific research due to their unique structure, low toxicity, and variety of biological activities. Consequently, the purpose of this chapter is to present the essential advancements in the use of natural products for the treatment of gout that have occurred recently, as well as to identify anti-HUA plants, their metabolites, and the structure-activity relationship with XOD. As a result, it is obvious that more detailed and advanced studies are needed for the development of anti-gout drugs in the future.